Comparative study of the effect of selected mutations on alpha-synuclein oligomerization in living cells using bimolecular fluorescence complementation (BiFC) assay - Rodrigues, Eva Sofia Ferreira (2012)
Dissertação de mestrado em Biologia Celular e Molecular, apresentada ao Departamento Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra